2017
DOI: 10.1111/jsr.12566
|View full text |Cite
|
Sign up to set email alerts
|

Sleep hygiene behaviours in Iranian adolescents: an application of the Theory of Planned Behavior

Abstract: SUMMARYPoor sleep quality and inadequate sleep in adolescents are a rising trend globally. The Theory of Planned Behaviour (TPB)-which centres on an individual's attitude toward performing the behaviour, subjective norms and perceived behavioural control-has been applied to examine sleep hygiene behaviours in young adults. We expanded on prior works by using a longitudinal design to examine the effects of TPB factors, together with sleep hygiene knowledge and planning constructs, on sleep hygiene behaviours an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 34 publications
5
54
0
Order By: Relevance
“…Specifically, the TPB constructs of attitudes, subjective norm, and perceived behavioral control significantly predicted hand washing and sleep hygiene intentions, while intentions further predicted hand washing and sleep hygiene behaviors. This is also in line with the findings of previous studies using the TPB to predict individuals' hand washing [37][38][39] and sleep hygiene [40][41][42]. It is also important to note that perceived behavioral control had a direct effect on sleep hygiene, consistent with TPB predictions [35].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, the TPB constructs of attitudes, subjective norm, and perceived behavioral control significantly predicted hand washing and sleep hygiene intentions, while intentions further predicted hand washing and sleep hygiene behaviors. This is also in line with the findings of previous studies using the TPB to predict individuals' hand washing [37][38][39] and sleep hygiene [40][41][42]. It is also important to note that perceived behavioral control had a direct effect on sleep hygiene, consistent with TPB predictions [35].…”
Section: Discussionsupporting
confidence: 89%
“…More specifically, and in the context of the current study, the TPB has been used to predict hand washing and sleep hygiene. For example, previous research has found support for the TPB constructs in predicting the intentions, and thus behavior, of caterers' [17], health care workers' [37,38], and nursing students' [39] hand hygiene, and adolescents' [40] and college students' [41,42] sleep hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…Strong et al. () provide us with very interesting data concerning sleep hygiene behaviours in adolescents living in Iran. By studying 1,822 healthy adolescents with a mean age of approximately 14 years, they investigated relationships between sleep hygiene behaviours, psychological variables and the construct they call the Theory of Planned Behaviour (TPB).…”
mentioning
confidence: 99%
“…Children sleep disorder (CSD) is one of the most common disorders in children. It has gained a growing trend in recent years around the world (1). Studies indicate that 10 -75 percent of children in the world suffer from CSD, which may be in the forms of simple bedtime resistance, frequent sleep-waking, parasomnias, and obstructive sleep apnea (2).…”
Section: Introductionmentioning
confidence: 99%
“…This tool, designed by Owens et al (13), indicates the status of children's sleep disorders according to the most common manifestations. Various studies were conducted in Iran concerning sleep and health status (1,(14)(15)(16). However, the status of CSD among 7-12-year-old children has not been studied.…”
Section: Introductionmentioning
confidence: 99%